The Role of Kyai Implementing Character Education at As-Suniyyah Islamic Boarding School - Hidayah, Sarofatul (International Proceedings of Nusantara Raya, 2022)
Pesantren is the oldest Islamic educational institution in Indonesia which has a noble purpose. Kyai as the leader of the Islamic boarding school plays an important role in developing character education for the students so that later after completing education at the Islamic boarding school it can be useful for the community, religion, country and nation. KH. Hisyam Tantowi is a compassionate and patient figure in educating the students, so many of the students or alumni admire him very much. This study departs from the actualization of the kiai's leadership role in character education of santri in Islamic boarding schools which consists of the role of rationality of purpose, spirituality and interpretation of the vision of education in Islamic boarding schools The method used in this study is a qualitative method in which the source of the results is obtained from interviews with predetermined sources. The results of this study prove that the Kyai's leadership role is very important for success in implementing character education in As-Suniyyah Islamic boarding schools, because of the example or real example given by the Kiai as the central leader in the Islamic boarding school and also the teacher council or ustadz and ustadzah who assist the Kiai in carrying out the wheels of education in the Islamic boarding school.